Detection of SARS-CoV-2 on the environmental surfaces and its implications for pandemic preparedness - Jamil, Kazi; Abdulrazack, Nasreem; Fakhraldeen, Saja; Kamal, Heba; Al-Mutairi, Anwar; Al-Feili, Batool; Ahmed, Imtiaz; Kumar, Vinod (Frontiers in Public Health, 2024)
Even though death due to COVID-19 is no longer a public health emergency, less virulent but highly transmissible forms of SARS-CoV-2 continue to spread in many countries leading to outbreaks and rise in hospitalizations in the affected regions. Lessons learned during the pandemic must be put into action to protect the world's population from another catastrophe like COVID-19. Novel approaches that were developed for tracking the spread of SARS-CoV-2 included analysis of wastewater, air samples, and various environmental surfaces. We conducted a study in Kuwait during the peak of COVID-19 pandemic to examine if SARS-CoV-2 could be detected in swabs taken from frequently touched environmental surfaces. We selected 12 Cooperative Society Stores—two from each governorate of Kuwait—for collection of surface samples. The Cooperative Society Stores are widely distributed across the whole country and cater to daily household needs including groceries and other essential items. These stores operated even during the “lockdown” imposed at the height of the pandemic. We collected swabs from high-touch surfaces including the handles of the shopping carts and freezers, the elevators, the keypads of the point-of-service terminals of cash counters, and the automated teller machines. All the surfaces tested showed a variable presence of SARS-CoV-2 by reverse transcriptase quantitative PCR, showing the validity of the proof-of-concept study. Monitoring of the presence of SARS-CoV-2 by surface sampling thus offers a cheap but effective means of environmental surveillance for coronaviruses. We therefore strongly recommend the addition of surface environmental sampling as a strategy for pandemic preparedness everywhere.